Manutenção de dois sistemas radiculares em aspectos bioquímicos e fisiológicos durante o desenvolvimento de plantas e desempenho agronômico de Passiflora edulis Sims enxertadas - Takata, William Hiroshi Suekane [UNESP] (2015)
Throughout this study, it was developed three experiments, which aimed to study the activity of antioxidant enzymes and gas exchange during the healing process in two grafting methods in passion fruit seedlings. After this period has been studied the development and growth of these seedlings, as well as the behavior of the photosynthetic apparatus. When the seedlings were grown, was rated the field agronomic performance, as well as fruit quality and their antioxidant potential, as well as the performance of the photosynthetic apparatus. The treatments were not grafted plants of Passiflora edulis Sims, conventionally grafted plants and grafted plants with maintaining two root systems, and the rootstock used to Passiflora gibertii. Based on the results obtained it was concluded that the use of grafted plants and maintaining two root systems provided yield and fruit quality equal to that of ungrafted plants. These plants throughout the healing process showed lower activity of antioxidant enzymes as well as shorter time for recovery of the photosynthetic apparatus. After healing, all treatments showed the same photosynthetic behavior.